2016
DOI: 10.1016/s2468-1253(16)30003-6
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab versus ciclosporin for steroid-resistant acute severe ulcerative colitis (CONSTRUCT): a mixed methods, open-label, pragmatic randomised trial

Abstract: SummaryBackgroundInfliximab and ciclosporin are of similar efficacy in treating acute severe ulcerative colitis, but there has been no comparative evaluation of their relative clinical effectiveness and cost-effectiveness.MethodsIn this mixed methods, open-label, pragmatic randomised trial, we recruited consenting patients aged 18 years or older at 52 district general and teaching hospitals in England, Scotland, and Wales who had been admitted, unscheduled, with severe ulcerative colitis and failed to respond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
1
27

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(194 citation statements)
references
References 30 publications
7
149
1
27
Order By: Relevance
“…Cyclosporine has long been shown as an effective rescue therapy in corticosteroid‐refractory acute severe colitis . An open‐labeled study comparing the two drugs did not show any significant difference in outcome, and this was confirmed in the CONSTRUCT study . Therefore, the choice of treatment is based on factors such as local availability, cost of therapy, and physician preference, whether patients have been unsuccessfully treated with thiopurines previously .…”
Section: Resultsmentioning
confidence: 91%
“…Cyclosporine has long been shown as an effective rescue therapy in corticosteroid‐refractory acute severe colitis . An open‐labeled study comparing the two drugs did not show any significant difference in outcome, and this was confirmed in the CONSTRUCT study . Therefore, the choice of treatment is based on factors such as local availability, cost of therapy, and physician preference, whether patients have been unsuccessfully treated with thiopurines previously .…”
Section: Resultsmentioning
confidence: 91%
“…Future research should focus on exploring findings from this study across a greater number and wide range of trial sites. It would also be beneficial to explore, following publication of the main trial findings, how views may have changed in the light of equal effectiveness across the two trial drugs being shown 29. How will this influence the preferences stated here and will it affect professionals’ decision-making between the two?…”
Section: Discussionmentioning
confidence: 99%
“…Although the CONSTRUCT trial did not find any difference in the length of stay with either therapy, patients and physicians noted greater treatment satisfaction with IFX 52. It seems very likely that the current evolution in our understanding and application of pharmacokinetics of IFX in ASUC will shape and favour the use of IFX as preferred salvage therapy in most units.…”
Section: Medical Managementmentioning
confidence: 94%
“…There was no statistically significant difference between the two for the primary end point as well as the secondary end point of colectomy rates, time to colectomy, serious adverse events or death. IFX, however, was associated with a greater cost of treatment as compared with ciclosporin 52. That said, biosimilars to IFX are now available and cost of therapy is reducing.…”
Section: Medical Managementmentioning
confidence: 99%